Barbados. Sugar Mile. (Old Process). - Cooper, W.G. (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
Picture of a sugar windmill on a plantation in Barbados. In the background a hut with a thatched roof is seen. Women and men are also seen in the background. At the front of the post card, printed in red ink "No.16. W.G. Cooper, Copyright". Also on the front bottom right in red ink "B. Series of 94." At the back of the post card on the top left-hand corner the following is written in pencil: CHP. £22-. The post card is divided into two with a double “T” shape and the words separately and printed in green. The words – THIS SPACE FOR CORRESPONDENCE AND FOR ADDRESS ONLY are both printed on each side of the division.
Landscape, Black & white, 5 1/2 x 3 1/2 inches.
Keywords: Historical markers; Sugarcane; Sugar plantations; Sugar industry; Mills; Food processing machinery; Historic buildings; Sugar mills